Practice of integrated vector surveillance of arthropod vectors, pathogens and reservoir hosts to monitor the occurrence of tropical vector-borne diseases in 2020 in Zhejiang Province, China - Wu, Yuyan; Wang, Jinna; Liu, Qinmei; Li, Tianqi; Luo, Mingyu; Gong, Zhenyu (Frontiers in Veterinary Science, 2022)
Abstract Background: Vector-borne diseases have become one of the most serious local public health threats. Monitoring and controlling vectors are important means of controlling vector-borne diseases. However, traditional vector surveillance system in China mainly monitor vector density which make its early warning effect on vector-borne diseases weak. In this study, we practised the integrated surveillance system of multiple arthropod vectors and reservoir host containing ecology, etiology and drug resistance monitoring to obtain better knowledge about the vector populations and to provide early warning of suspicious vector-borne infectious disease occurrence. Methods: An ecology surveillance of mosquitoes, rodents, ticks, and chigger mites, a pathogen infection survey on mosquitoes and rodents, and a drug resistance survey on Aedes albopictus were conducted in 12 cities in Zhejiang Province in 2020. Results: A total of 15645 adult mosquitoes were collected, with a density of 19.8 mosquitoes per Centers for Disease Control and Prevention light trap, and Culex tritaeniorhynchus (72.76%) was the most abundant species. The Breteau index of Ae. albopictus was 13.11. The density of rodents was 0.91 rodents per hundred traps, and the most abundant species was Rattus norvegicus (33.73%). The densities of dissociate and ectoparasitic ticks were 0.79 ticks per hundred meters and 0.97 ticks per animal, respectively. The most abundant tick species was Haemaphysalis longicornis (56.38%). The density of chigger mites was 14.11 per rodent, and two species were identified, with the most abundant species Walchia spp.mite (68.35%). In mosquito etiology monitoring, no Flavivirus or Alphavirus was found, whereas the positivity rates of Hantavirus, pathogenic Leptospira, Orientia tsutsugamushi, and Bartonella in rodent etiology monitoring were 1.86%, 7.36%, 0.35% and 7.05%, respectively. Field populations of Ae. albopictus in Zhejiang Province were widely resistant to pyrethroids, but sensitive to most insecticides tested, including organophosphorus and carbamate insecticides. Conclusions: Integrated surveillance systems of on multiple arthropod vectors (mosquitoes, ticks, mites) and animal reservoirs (rodents) can provide important information for the prevention and control of epidemic emergencies.